The teaching of rural extension in debate: new epitesmological frontiers? (Semiárida, 2023)
This note analyzes current discussions on the teaching programs of Rural Extension in university careers. It reports on the changes promoted by decision-making agencies and the debate produced by the incorporation of new contents to the discipline. For this purpose, it summarizes the presentations made at the Permanent Seminar of Rural Extension Trainers held at the Faculty of Agronomy of the UNLPam.
Keywords: rural extension; disciplinary boundaries; teaching programs